Membangun Kesadaran Digital: Sosialisasi Sertifikat Tanah Elektronik di Desa Candiwatu - Ramadhani Dwi Pangestu; Mangruwa Wati, Tan Hana Darma; Maulidan, Ardhani Ahimsha; Sri Diyanti, Daffa Dwi (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2025)
Public land services in Indonesia, particularly the issuance of land title certificates, face significant challenges related to efficiency and transparency. To address these issues, the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) launched an electronic land certificate program as part of its digital transformation. A community service program (KKN) in Candiwatu Village aimed to increase public understanding of this policy. Through a participatory approach, the outreach program successfully raised public awareness of the benefits of electronic certificates, such as data security, service efficiency, and ease of verification. Despite concerns about digital data security and technological accessibility, community enthusiasm demonstrated a willingness to adapt to the new system. This initiative is expected to be a starting point for the digitalization of land services at the village level and encourage further collaboration between the government and communities.